"Hansel and Gretel” - Tratnik, Polona (Acta Histriae, 2023)
“Hansel and Gretel” begins with the parents’ decision to abandon their children. The author argues that the differences in how the children survive their exile reflect the changes in how modern societies conceptualized their organization. An early baroque tale speaks of a contracted civil society and legitimizes sovereign power, while later versions represent Enlightened social subjects capable of emerging from their minority. The motif of abandoned children reaches back to Roman antiquity, where it was linked to mimetic rivalry. The author shows in what ways mimetic rivalry appears in modern fairy tales.
Keywords: Basile, Giambattista; evropska mitologija; Grimm, Jacob; Grimm, Wilhelm; Grimmove pravljice; mimetično rivalstvo; Montanus, Martin; Perrault, Charles; pravljice; pravljično izročilo; razsvetljenstvo